Who directs group movement? Leader effort versus follower preference in stickleback fish of different personality - Nakayama, Shinnosuke (Biol Lett, 2016)
During collective movement, bolder individuals often emerge as leaders. Here, we investigate whether this reflects a greater propensity of bold individuals to initiate movement, or a preference for shy individuals to follow a bolder leader. We set up trios of stickleback fish comprising a focal individual who was either bold or shy, and one other individual of each personality. We then recorded the movements of all individuals in and out of cover in a foraging context to determine how assiduously the focal fish followed the movements of each other partner. We found that a shy focal fish preferred to follow a leader whose personality matched its own, but we did not detect such a difference in bold fish. Despite this preference, however, the greater propensity of bold individuals to initiate movements out of cover meant that they successfully led more joint trips. Thus, when offered a choice of leaders, sticklebacks prefer to follow individuals whose personality matches their own, but bolder individuals may, nevertheless, be able to impose their leadership, even among shy followers, simply through greater effort.